PEMBERDAYAAN PETANI SACHA INCHI SECARA SWADAYA DI DESA PENGGUNG KECAMATAN NAWANGAN KABUPATEN PACITAN JAWA TIMUR - Noer Soetjipto; Deddy Rusdiana; Yoesoep Edhie Rachmad; Mohammad Soleh Ridwan (Yayasan Education and Social Center, 2023)
Stunting, or chronic malnutrition in children, is a serious health problem in Indonesia. According to data from the Indonesian Ministry of Health in 2020, the prevalence of stunting in Indonesia reached 27.7%. This figure indicates that around 9.8 million children in Indonesia suffer from stunting. One functional food group that has an impact on the immune system is omega-3 fatty acids. The highest dietary sources of omega-3 fatty acids are usually obtained from marine animal sources such as salmon. However, not only marine animal sources, plant sources also contain high levels of omega-3 fatty acids such as plant sources from the Sacha Inchi plant (Plukenetia volubilis L.). The problem is Sacha Inchi is not a familiar crop commodity for farmers. Most farmers grow more common crops such as rice, corn, peanuts, and some vegetables. An optimal and reliable empowerment method or approach is needed to encourage farmers to contribute to reducing the incidence of stunting in Indonesia. Therefore, farmer empowerment in growing Sacha Inchi is necessary to contribute to efforts to reduce stunting rates in Indonesia, including in the Penggung Village of Nawangan District, Pacitan Regency, East Java. This study shows that farmer empowerment using Micro, Mezzo, and Macro levels carried out in Penggung Village of Nawangan District, Pacitan Regency, East Java can be considered successful. The main driving factor for success is the support of the village officials to support the program. Meanwhile, the obstacles come from the low quality of human resources and unpredictable weather